THE SPIRITUAL PSYCHOLOGICAL APPROACH TO DRUG ADDICTS - Iredho Fani Reza; Annisa; Iffa Silfi Ulinnimah; Hilya Halimatus Saadah; Yunita Carolina; Sheva Semara Simatupang; Dwina Florensia; Yuniza Eka Putri Larasati; Sulaiman Indrawan; Sukma Utama; Mia Firauhinnur; Putri Raeka Aziza Barus; Dicko Meilandara; Khadijah Ramadesfa; Tezzy Maria Sinta; Luthfiyyah Anjeli (Journal of Islamic Psychology and Behavioral Sciences, 2023)
The purpose of this study is to determine the level of spirituality (religion) that exists in former drug users, by giving this spirituality it is hoped that they will be aware of the dangers of drugs and be able to get closer to God. This study uses qualitative methods with observation data analysis techniques and semi-structured interviews. Determination of purposively selected informants, namely foundation management, former drug addicts who are in the process of rehabilitation and assistants or counselors. Data collection by interview, observation and Focus Group Discussion (FGD) and we also found that the Ar-Rahman Drug Rehabilitation Center can be used as an alternative in spiritual and herbal (non-medical) rehabilitation of drug abuse. Spiritual rehabilitation uses a humanist and familial approach so that drug addict patients can be open, close and trust the counselor in the therapy process. The results and discussion are that former drug addicts at YPRN Ar Rahman Palembang have a low level of understanding of spirituality. In terms of the discussion with the religious teacher at YPRN Ar-Rahman, it was found that the client did not yet have the ability to understand spirituality, only limited to ritual formalities. This is further strengthened by the results of interviews we conducted with direct clients, that they actually believe in God, but do not fully believe in God.